2011
DOI: 10.1097/igc.0b013e31822a0195
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Genotype Distribution and Human Papillomavirus 16 and Human Papillomavirus 18 Genomic Integration in Invasive and In Situ Cervical Carcinoma in Human Immunodeficiency Virus-Infected Women

Abstract: The prevalence and distribution of principal HPV types involved in the carcinogenesis process of the cervix were similar in HIV-infected and noninfected women, although a tendency toward a lower HPV-16 and a higher HPV-18 prevalence in invasive cervical carcinoma was detected in HIV-positive women. Similar percentage of HPV-16 and HPV-18 viral integration was found in formaldehyde-fixed paraffin-embedded specimens of cervical cancer regardless of the HIV infection status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Furthermore, the quality of conservation of histology samples and the techniques used for DNA extraction and HPV testing can considerably influence variability in prevalence. Consistent with other authors [1] [15], we found that HPV-18 was rare (only 1 case in a non-HIVinfected woman), thus reinforcing the fact that HPV-18 is more common in cervical cancer than in anal SCC [20]. Moreover, mean age at the diagnosis of anal ISCC was significantly lower for men than for women, as re-ported elsewhere [18]; however, we did not observe this effect of HIV infection on age, probably because of the small sample size and the composition of the HIV-infected group.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the quality of conservation of histology samples and the techniques used for DNA extraction and HPV testing can considerably influence variability in prevalence. Consistent with other authors [1] [15], we found that HPV-18 was rare (only 1 case in a non-HIVinfected woman), thus reinforcing the fact that HPV-18 is more common in cervical cancer than in anal SCC [20]. Moreover, mean age at the diagnosis of anal ISCC was significantly lower for men than for women, as re-ported elsewhere [18]; however, we did not observe this effect of HIV infection on age, probably because of the small sample size and the composition of the HIV-infected group.…”
Section: Discussionsupporting
confidence: 92%
“…According Darwich L et al [25] there is a high prevalence of HPV 16 and 18 in cervical cancers in HIV positive and negative women in Barcelona. In ICC the HPV 18 was significantly more prevalent in HIV-positive women as opposed to HIV-negative women (14% vs 1%).…”
Section: Discussionmentioning
confidence: 99%
“…The sparse data from ICC cases reported from outside Africa (14 cases in Spain, 36 5 in India, 37 and 5 in the United States 6,20,38 ) are not reported here.…”
Section: Methodsmentioning
confidence: 95%